Samuel E. Asbury papers - Asbury, Samuel E. (Samuel Erson), 1872-1962.
Typewritten transcripts of correspondence and notes relating to Asbury's search for documents concerning the history of Texas.
Typewritten transcripts.
Historian.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Texas -- History -- Sources; Historians